Hepatotoxic Assessment of Pecralima nitida Seeds Supplemented Diet in Wistar Rats. - S. Ezekwe Ahamefula, C. Chukwu Ezinne, U. Osuocha Kelechi (Journal of Medicinal Herbs and Ethnomedicine, 2017)
This study assessed phytochemical constituents of Pecralima nitida seed extract and its effect on liver enzymes activities of male albino rats fed Pecralima nitida seed supplemented diet. A total of twenty male albino rats were used for this study and were randomly divided into four groups of five rats each. Group I was fed with normal rat feed and water, group II was fed with 50% pecralima nitida seed and 50% normal rat feed, group III was fed with 70% pecralima nitida seed and 30% normal rat feed while group IV was fed with 90% sample and 10% normal rat feed for a period of twenty eight days. The preliminary phytochemical profile showed the presence of flavoniod, saponin, tainins, glycoside, alkaloid, phenol and steroid. These bioactive compounds may contribute to the reputed medicinal efficacy of pecralima nitida seed. Liver enzymes activities such as AST showed no significant difference between the control (24.39 ± 3.6IU/L) and group II (25.88 ± 3.7IU/L) but significantly increased in group III (37.38 ± 7.2IU/L) and group IV (42.19±2.1IU/L). The other enzymes ALT and ALP showed significant statistical increase in groups II-IV (P<0.05). The histological evaluation shows that group III and IV had evidence of degenerative tissues induced by 70% sample and 30% normal rat feed and 90% and 10% normal rat feed. This however showed and suggested that irrespective of the reputed medicinal relevance of pecralima nitida seed, care should be taken in the quantity of these extract that is consumed as this may exhibit cumulative toxicity leading to functional impairment in the integrity of the liver.